Efeito do tratamento com losartan sobre o desenvolvimento folicular de ratas wistar adultas, com obesidade induzida pela dieta de cafeteria - Gobo, Cristiane Gisselda (2015)
The prevalence of obesity has increased in recent decades in many countries, and harmful effects to the body can begin in childhood and persist into adulthood. Obesity is associated with disturbances of reproductive function in women and in female rodents, such as early onset of puberty, change in menstrual / estrous cycle and infertility, with impaired ovulation or anovulation (lack of ovulation). Angiotensin II (Ang II) appears to exert effects on reproduction and obesity, contributing to the development of the deleterious effects of obesity and affecting pre-ovulatory surge of luteinizing hormone (LH), estradiol and progesterone, thus reducing ovulation in adult rats. The objective of this study was to evaluate losartan effect, an antagonist of Ang II AT1 receptor, administrated in adulthood, in follicular development of adult Wistar rats with obesity induced by cafeteria diet. After weaning at 21 days of life, female Wistar rats were divided into 02 groups: control (CTL) that received standard chow diet; Cafeteria (CAF) received the cafeteria diet. From 70 days of life began losartan administration by gavage. The CTL group received water in gavage (CTL) and CAF group was separated into 02 groups, CAF (which received water in gavage) and CAF + LOS (who received losartan in gavage), in total 03 groups were performed. 05 animals were used per group. Euthanasia was performed on the first proestrous after 30 days of administration of losartan or water. The retroperitoneal, perigonadal and subcutaneous fat were removed and weighed. Morphological analysis of ovaries was performed, proceeding to count the number of primary follicles, secondary, antral and mature follicles per ovary. Was also collected blood sample for determination of FSH, LH, prolactin and progesterone. Body weight and the weight of the 03 fats were measured, and the number of antral follicles were higher in group CAF in relation to the group CTL (p <0.001). However, FSH and LH levels were lower in the CAF animals compared to the animals of the group CTL (p <0.001). The administration of losartan normalized the body weight and accumulation of retroperitoneal and subcutaneous fat as well as the number of antral follicles. Thus, we suggest that the use of the antagonist of Ang II AT1 receptor, losartan, in adulthood, can improve follicular development in females with cafeteria diet-induced obesity and, can be, in the future, an coadjuvant drug in the treatment of infertility associated to obesity.